An algorithm for determining the oxygen concentration in the Black Sea by Argo probes - Nikolov, Nikolay (Annual of Natural Sciences Department, 2021)
This paper presents the algorithm for determining the concentration of dissolved oxygen in the Black Sea according to data from Argo probes. A comparison was made between data from two Argo probes released in the Black Sea in 2011 and 2014.